Self-Selection in Conflict-Induced Migration: Micro Evidence from Bosnia - Nermin Oruč (The Vienna Institute for International Economic Studies (wiiw), 2009)
This paper aims at contributing to the analysis of brain drain by focusing on countries in conflict. Here, experiences of migrants from Bosnia have been collected in order to identify specific determinants and patterns of migration in the conflict settings. Then, these observations were used to develop a theoretical model of conflict-induced migration, which identify possible mechanism of self-selection of migrants. Finally, a micro-level analysis of determinants of conflict-induced migration from Bosnia has been conducted, in order to provide empirical evidence for the theoretical model. The analysis was based on the World Bank's BiH LSMS 2001 household survey data. The main aim of this study was to identify possible self-selection mechanism of conflict-induced migration and its impact on the migration rates of highly skilled individuals. The empirical evidence supports the theoretical prediction of a mechanism of self-election present in the conflict-induced migration setting.
Keywords: 330; migration; conflict; brain drain; self-selection; relative deprivation; multinomial logit